2013
DOI: 10.3747/pdi.2012.00105
|View full text |Cite
|
Sign up to set email alerts
|

Localized Encapsulating Peritoneal Sclerosis Constricting the Terminal Ileum—an Unusual Appearance Requiring Surgical Intervention

Abstract: ♦ Background: Encapsulating peritoneal sclerosis (EPS) is a rare complication of peritoneal dialysis (PD). It is characterized by encapsulation of the bowel, causing symptoms of intestinal obstruction. Exclusive involvement of parts of the bowel may occur and may be more common than previously thought. Our main objective was to investigate and report on patients with localized EPS. ♦ Methods: Between July 2002 and December 2011, 9 of 17 EPS patients were referred to our department of surgery for a diagnostic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Similarly Habib et al reported 3 cases of “localized” EPS, where intra-operatively, an obvious sclerotic and thickened peritoneal membrane was observed, predominantly covering and constricting the terminal ileum [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly Habib et al reported 3 cases of “localized” EPS, where intra-operatively, an obvious sclerotic and thickened peritoneal membrane was observed, predominantly covering and constricting the terminal ileum [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Latus et al (6) propose categorizing EPS based on three different physical appearances; however, those appearances do not cover the full range of presentations, others of which are described by Habib et al (7). The appearance of the peritoneal cavity in EPS that is encountered at surgery can be described in terms of each of the following elements: The large bowel may be affected by sclerosis and tanning, but is rarely obstructed.…”
Section: Classification Of Encapsulating Peritoneal Sclerosis Is Impomentioning
confidence: 99%
“…In this edition of Peritoneal Dialysis International , two papers describe the varying manifestations of EPS at the time of surgery (6,7). One describes a localized form of the disease; the other suggests classifying EPS into three patterns based on its appearance, but interestingly does not distinguish between localized and generalized disease.…”
mentioning
confidence: 99%
“…Additionally, the CT scan showed a small amount of localized ascites in the abdomen but no other diagnostic signs of EPS like bowel tethering, calcifications, or peritoneal thickening. Despite the absence of typical findings, but the severity of the progressive symptoms we considered the possibility of localized EPS, a condition in which the peritoneum shows encapsulating sclerosis predominantly at the level of the terminal ileum [ 13 , 14 ]. Surgical exploration was considered as a final diagnostic procedure.…”
Section: Case Presentationmentioning
confidence: 99%